The force that stretches the cord is the weight of the bungee jumper, which is given by:
![F=mg](https://img.qammunity.org/2019/formulas/physics/middle-school/eorfe9r4ylohwnsavdioh6jmghfu1eat50.png)
where m is the mass of the jumper and g the gravitational acceleration. Substituting, we find
![F=mg=(68 kg)(9.81 m/s^2)=667.1 N](https://img.qammunity.org/2019/formulas/physics/high-school/5zdg7eypkot2fhg4coxna79geuy06d7b9y.png)
This force is equal to the elastic force that stretches the cord:
![F=kx](https://img.qammunity.org/2019/formulas/physics/high-school/jupx88svo64nevelqzouguq4ki0vyb3tm6.png)
where k is the spring constant and x is the elongation of the cord. Rearranging the equation, we find x:
![x= (F)/(k)= (667.1 N)/(54 N/m)=12.4 m](https://img.qammunity.org/2019/formulas/physics/high-school/2eud6b9l1gycnav9uhgq8vfvivm01dopgm.png)